Gymnastics Assistance for the Independent Elderly: Service in Efforts to Prevent Dementia in Bulak Village, Surabaya - Utomo, Bedjo; Soetjiatie, Liliek; Sulistijono, Heru; Hindaryani, Nurul (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Degenerative diseases are infections that almost occur in old age, with decreased physiological function will have an impact on several chronic diseases, such as hypertension, diabetes, osteoarthritis, Alzheimer's, heart disease, kidney failure, therefore, to prevent the occurrence of these diseases it is necessary to strive for promotive, preventive, and rehabilitative measures. One of the efforts made is to carry out community service in the form of assisting the elderly so that they can live independently and have a good quality of life. Community service for Departemen of health Poltekkes Kemenkes Surabaya which was carried out at RW 2 Bulak Village in the form of counseling, health checks, nutrition fulfillment education and elderly gymnastics. The results of counseling education about degenerative diseases and their prevention have shown a 90% good level of understanding, and the elderly have high enthusiasm to participate in gymnastics movements and do health tests. Furthermore, the continuation of this activity is expected to be followed up by improving effective communication between puskesmas officers, elderly cadres so that the elderly program can run optimally